Biphobia in sport - Sexual identity and exclusionary practices - Maddocks, K. L. (2013)
Research in the field of bisexuality has identified that bisexuals experience a unique kind of phobia, in that phobic responses to their sexual preferences appear from both mainstream and LGBT communities. However, little research in the UK has been conducted within the arena of sport culture to cater for the particular welfare needs of bisexual athletes. As an additional consequence, there is little theorisation of bisexuality available within the context of sport sociology. This research contributes to debates in the politics of identity by exploring a fairly new landscape within sport culture using a Foucauldian analysis of power. Discourse analyses have been utilised to interpret thirteen semi-structured interviews conducted with British athletes on the topics of bi-invisibility and the general problem of homophobia. This research also contributes to discussions concerning the mobilisation of power through discourse - certain discursive practices function to legitimize normative over non-normative sexualities and queer/fluid/bisexual identities are further stigmatized and othered. The main findings suggest that exclusions are mobilised most effectively, ironically, through sport cultural practices of inclusion, in that they are almost exclusively sexual identity-based. Additionally, this study offers a theoretical explanation for the peripheralisation of bisexuality in sport culture which can shed new light on bisexual theory in mainstream culture. It makes important suggestions as to the new directions future research can take in order to advance the current knowledge bases concerning the effects of bantering. This research proposes that practices of bantering can be just as marginalising as those of bullying. In the resultant climate of covert exclusions, organizational sporting bodies could benefit from paying close attention to the disempowering effects of biphobic and homophobic language, whether humorously intended or otherwise. This is with particular respect to youth footballing academies and spectator communities.